Penerapan Metode Membacakan Buku Cerita Untuk Meningkatkan Kemampuan Literasi Anak Usia Lima Sampai Enam Tahun di Tk XYZ [Application of the Story Book Reading Method to Improve the Literacy Skills of Five to Six Year Old Children in XYZ Kindergarten] - Sitohang, Eunike Maria Kristine; Listiyani, Anastasia; Nurhayati, Chicilia (Jurnal Teropong Pendidikan, 2023)
The results of the Organization for Economic Co-operation and Development (OECD) research on the literacy test of Indonesia's Program for International Student Assessment (PISA) show that Indonesia's literacy ability is still low. Literacy skills are needed as a twenty one century skill that must be mastered from an early age. One way to increase literacy is to read storybooks. This study aims to analyze the relationship between the method of reading storybooks to early childhood literacy skills. The method used in this study is quantitative descriptive by distributing questionnaires using five Likert scales (always, often, sometimes, rarely, never). The research was conducted in a private kindergarten in Central Jakarta with a research subject of one hundred and nine students. The results of the research obtained are that there is a relationship between the method of reading storybooks to early childhood literacy skills. The longer the duration of reading stories to children, the higher their literacy skills. Therefore, the method of reading storybooks should be done with a longer duration and frequently, so that children's literacy skills can be maximized.